Ameliorative effects of agomelatine against doxorubicin-induced hepatotoxicity - Hasan Basri Savas; Mehmet Enes Sozen; Gokhan Cuce; Tuba Batur (BMC Pharmacology and Toxicology)
Abstract Drug-induced hepatotoxicity is a significant impediment to the use of doxorubicin, a commonly employed chemotherapeutic agent with established efficacy in cancer treatment. The present study aimed to determine the potential protective effects of agomelatine against doxorubicin hepatotoxicity in rat toxicity models. Thirty-two rats were divided into four groups: control (with saline administration), Doxo (with 40 mg/kg doxorubicin administration), Doxo + Ago20, and Doxo + Ago40 (with 20 and 40 mg/kg agomelatine administration and 40 mg/kg doxorubicin administration). On the day of 14 rats were sacrificed, samples were collected for comparison of immunohistochemical, hematological, and biochemical analysis. There were statistically significant differences between the study groups in terms of immunohistochemical, hematological, and biochemical parameters. Agomelatine administration reduced the TNF-alpha, and caspase-3, which increased by doxorubicin, and reversed levels of oxidative stress markers altered by doxorubicin (p < 0.05). Doxorubicin induces oxidative stress, apoptosis, and hepatotoxicity. Agomelatine may be favored as a primary antidepressant to mitigate hepatic damage induced by doxorubicin.